Bessel Beam Generation Using Dielectric Planar Lenses at Millimeter Frequencies - Alvaro F. Vaquero; Marcos Rodriguez Pino; Manuel Arrebola; Sergio A. Matos; Jorge R. Costa; Carlos A. Fernandes (IEEE Access, 2020)
In this work a dielectric planar lens is proposed to generate a Bessel beam. The lens works at Ka-band and produces a non-diffraction range within the Fresnel region of the antenna. The methodology to design the aperture antenna at millimetre or microwave frequencies is presented. It is applied to a dielectric planar lens made up of cells that shapes the radiated near-field by adjusting the unit cell response. An approach based on a second order polynomial is proposed to consider the angular dependence of the phase-shift response of the cell in the designing process. In order to implement the lens physically, two novel cells, based on rectangular and hexagonal prisms, are proposed, and their performance is compared. The cells ensure the index dielectric media variation using airgaps to control the overall density of the material. After fully characterizing the cells, a design is carried out for the two proposed type of cells. The requirement for the Bessel beam is a depth-of-field of 650 mm at 28 GHz. After evaluating the design in a full-wave simulation, both prototypes were manufactured using a 3-D printing technique. Finally, the prototypes were measured in a planar acquisition range to evaluate the performances of the Bessel beam. Both lenses show a good agreement between simulations and measurements, obtaining promising results in the Bessel beam generation by index-graded dielectric lenses at Ka-band.